PENGARUH KOMPETENSI, MOTIVASI KERJA, DAN LOYALITAS TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN DAERAH PASIR PUTIH KABUPATEN SITUBONDO - Abdul Malik Jazuli; Mohammad Yahya Arief; Lita Permata Sari (Jurnal Mahasiswa Entrepreneurship (JME), 2025)
The background of this research is that the main problem in human resource management that deserves attention is employee performance. Employee performance is considered important for the company because the success of a company is influenced by the performance of the employees themselves. This research was conducted with the aim of knowing the partial, simultaneous, and dominant influence of Competence, Work Motivation, and Loyalty on Employee Performance at Regional Company the Pasir Putih, Situbondo Regency. The research method used is the method of observation, literature study, and documentation. The data analysis method used validity test, reliability test, classical assumption test, multiple linear regression analysis, hypothesis test, dominant test, and coefficient of determination. Based on the results of multiple linear regression shows that the variables Competence (X1), Work Motivation (X2) and Loyalty (X3). Y = -1.102E-16 + 0.530X1 + 0.235X2 + 0, 240X3 + e. The tcount for this Competency variable is 3.929. While the value in the 5% distribution ttable is 2.048, then tcount 3.929 > ttable 2.048 means Ho is rejected or Ha is accepted. The t-value for this Work Motivation variable is 2.381. While the value in the 5% distribution ttable is 2.048, then tcount 2.381> ttable 2.048 means Ho is rejected or Ha is accepted. Meanwhile, the tcount value for this Loyalty variable is 2,920. While the value in the 5% distribution ttable is 2,048, then tcount 2,920 > ttable 2,048 means Ho is rejected or Ha is accepted. Comparing the value of Fcount (69.893) > Ftable (2.92) based on statistical testing using the f test method, where the significant level obtained is 0.000 < 0.05. Showing the value of the coefficient of determination R square shows a value of 0.875, from these results it means that all independent variables (Competence, Work Motivation, and Loyalty) have a contribution of 87.5% to the dependent variable (Employee Performance) with a sufficient level of determination, and the remaining 12 ,5% influenced by other factors not included in the study.